Radio‐frequency energy harvesting potential: a stochastic analysis. Issue 5 (10th April 2013) - Guo, Weisi; Wang, Siyi
ABSTRACT: This paper considers the energy harvesting potential from ambient electromagnetic waves in the radio frequency (RF) communications spectrum. Because of chaotic positioning nature of cells, handsets and hotspots, the analysis employs stochastic geometry theory to derive the mean and probability distribution of the received RF radiation energy available for harvesting. The mean and density function of energy harvested, as a function of transmitter deployment density, spectrum and pathloss characteristics are given. The novel benefit is that the derived expressions serve as a design guideline for RF harvesting solutions. For a given power harvesting and reliability requirement, the expressions in this paper can yield insight into which set and how many RF spectrum bands to harvest. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This paper examines the theoretical probability distribution of crowd‐harvesting radio energy from multiple networks and sites. The results show that under current urban scenarios, approximately 1mW can be harvested with no shadow fading and 1 μ W with urban log‐normal shadowing. The conclusion is that realistic energy harvesting of radio signals in most deployment scenarios provides inadequate power for existing sensor devices.